A CONTRIBUTION TO THE DEBATE ON THE POLICY OF SANCTIONING CORPORAL PUNISHMENT OF CHILDREN IN SERBIA: ATTITUDE INCONSISTENCY - Stajkić, Dr Bojana; Hrnčić, Jasna; Blagojević, Milena (Serbian political thought, 2024)
The policy of introducing a prohibition on corporal punishment of children (CPC) into legal frameworks currently needs unanimous support among social actors in Serbia. This may reflect the instability and inconsistency of collective and individual attitudes toward CPC, which are in the process of changing. The subject of this research is the attitude toward CPC from the standpoint of social change theories and stages of the attitude change process. The aim was to examine the consistency of this attitude across different levels of generality and situational contexts to determine its stability. A quantitative study was conducted among 104 respondents. Data were collected through an online questionnaire designed for the research. The findings revealed that attitude toward CPC depends on situational context differences and the context’s specificity level. For instance, while 79.8% of respondents hold a negative general attitude toward CPC, 54.8% believe that parents should legally be allowed to slap a child on the buttocks with an open hand when the child is disobedient. When presented with five different situations involving specific child misbehavior, only 1.9% to 6.7% of respondents approved of a parent’s reaction involving a mild slap on the buttocks without further explanation, depending on the situation. Conversely, support for this reaction increased to between 7.7% and 31.7% if accompanied by an explanation of why the child’s behaviour was inappropriate. The results of the inconsistency of attitudes toward CPC are discussed in light of the significance of the level of abstraction and situational context. The recommended approach advocates for a policy that respects the particularities of Serbian society by formulating legal provisions on CPC as precisely as possible.
Keywords: politika zabrane fizičkog kažnjavanja; deca; vaspitavanje; disciplinovanje; promena stava; zakon